FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KADER DALAM PELAKSANAAN POSYANDU BALITA DI DESA JAYALAKSANA WILAYAH KERJA PUSKESMAS CABANG BUNGIN KABUPATEN BEKASI PROVINSI JAWA BARAT TAHUN 2017 - Marini Madiastuti; Anita Ekalaningsih (Universitas Nasional, 2017)
Background: Integrated Service Post (Posyandu) is a container of health care conducted, by and for the community guided by related officers. (Ministry of Health RI) Activities in Posyandu are highly dependent on the role of cadres. Kader is a volunteer from the community. The achievement of children under five is nationally weighed 80,8%. For the Province of Bali there are 4,783 posyandu with achievement of underweight exceeded national achievement figure that is equal to 87%. The number of Integrated Service Post (Posyandu) is 310,737 posyandu (Ministry of Health, 2013). The purpose of this study is to look at factors related to the activeness of cadres in the implementation of Posyandu Balita in Jayalaksana Village Working Area Puskesmas Cabangbungin Bekasi Regency West Java Province in 2017. The method used is quantitative research with analytic survey, using cross sectional design with population 40 cadres Data analysis to see the relationship between the variables studied. Result of univariate analysis showed less active cadre (67,5%) while active (32,5%), lowest education 55%, unsupportive family support 60%, unfavorable motivation 52,5 % And awards are not given as much as 62.5%. The result of bivariate analysis shows. There is a significant relationship between education (p-value 0,000); Family support (p-value 0,000); (P-value 0,000) and between cadre motivation (p-value 0,025) with cadre activation in posyandu Toddler in Jayalaksana Village Working Area of Puskesmas Cabangbungin Bekasi Regency 2017. Suggestion: Village Head as party having authority and moral in village environment It is expected to provide good support for the cadres who are active in posyandu activities and for health workers to directly provide information about posyandu problems to the cadres so as to increase the motivation of cadres which will be themed the activity of posyandu cadres.